Emissions to Air in a Seaport – An Approach to Modelling, Quantification and Reduction - Deda ĐELOVIĆ (Promet (Zagreb))
Emission sources associated with port operations are very different and ports are obliged to develop adequate responses. After a general introduction, an overview on literature related to emissions to air in ports and summary of already implemented responses (solutions) on port related emissions, the interdependency between the quantity of CO2 emitted by mobile harbour cranes during loading process of vessels is modelled, implementing the multiple regression model. Parameters of the model show that 88.53% of the variability of the quantity of the emitted CO2 to air per vessel depends on selected independent variables. Results presented in this paper enable recognition of some directions of reduction of CO2 emissions to air by the cargo handling equipment in a port. Furthermore, a planning tool purposed for quantification and forecasting CO2 emissions from cargo handling equipment in a port, based on a group of relevant parameters, is proposed. In that context, the influence of variations in productivity in the cargo handling process on the quantity of CO2 emitted to air is analysed. The proposed approach can be implemented in other ports where the diesel-powered cargo handling equipment is in use. In addition, the presented results can be a reliable base for further engagement of the author in this domain.